(untitled) (Research, Society and Development, 2022)
The class of benzodiazepines is among the most consumed drugs in Brazil and in the world. Developed accidentally in the 1960s, these drugs were well accepted for their satisfactory effects in controlling sleep disorders and anxiety. Due to the growing number of diagnoses of disorders related to sleep and anxiety, as well as the practice of self-medication, the abusive consumption of benzodiazepines is increasing, which consequently causes serious health problems such as tolerance, withdrawal, dependence, among others. The objective of this review is to compare the existing literature on dependence in the long-term use of benzodiazepines in the treatment of anxiety in elderly patients, highlighting Clonazepan versus Diazepam. For the bibliographic research, LILACS, PUBMED/MEDELINE and SCIELO databases were used, in which 32 articles were identified, 20 of which were used in the elaboration of the work, with the selection of articles published in national and international journals, in the period of 2013 to 2022. Results show the dependence and consequences of long-term use by elderly patients who use benzodiazepines, as well as the difficulty of management in the discontinuation of the elderly. The literature suggests the safe and effective use of benzodiazepines in elderly patients with anxiety, in order to prevent their dependence.